Study on optical properties and energy transfer of Dy\(^3+\) ions in ZnS semiconductor nanocrystals - Trinh, Thi Thu Huong; Nguyen, Thi Hien; Xuan Ca, Nguyen (Communications in Physics, 2025)
In this study, Dy³⁺-doped ZnS nanocrystals (NCs) with concentrations varying from 0.5-3% were successfully synthesized by the wet chemical method in a pure Ar atmosphere. XRD and EDX results showed that the material crystallized in a stable cubic phase, with nanometer size, and determined the presence of elements in the sample. FTIR spectra recorded characteristic vibrational bands of Zn–S bonds and surface organic functional groups, confirming the formation of ZnS host and a stable organic coating surrounding the nanoparticles. UV-Vis absorption spectra confirmed the distinct quantum confinement effect compared to bulk ZnS. Photoluminescence (PL) spectra of the sample showed characteristic emission lines of Dy³⁺, in which the gold peak at 580 nm was dominant. The CIE color coordinate and correlated color temperature (CCT) analysis results showed the ability to tune the color from cool blue light of pure ZnS to warm white light when doped with Dy³⁺. The fluorescence quenching that occurred at Dy concentrations above 2% and the decrease in fluorescence lifetime with increasing Dy concentrations were explained through cross-relaxation energy transfer processes in Dy³⁺ ions. These characteristics demonstrate that ZnS:Dy³⁺ NCs are promising luminescent materials for white light LEDs and advanced optoelectronic applications.